(9x-6)+(-8x+4)=7

Simple and best practice solution for (9x-6)+(-8x+4)=7 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (9x-6)+(-8x+4)=7 equation:


Simplifying
(9x + -6) + (-8x + 4) = 7

Reorder the terms:
(-6 + 9x) + (-8x + 4) = 7

Remove parenthesis around (-6 + 9x)
-6 + 9x + (-8x + 4) = 7

Reorder the terms:
-6 + 9x + (4 + -8x) = 7

Remove parenthesis around (4 + -8x)
-6 + 9x + 4 + -8x = 7

Reorder the terms:
-6 + 4 + 9x + -8x = 7

Combine like terms: -6 + 4 = -2
-2 + 9x + -8x = 7

Combine like terms: 9x + -8x = 1x
-2 + 1x = 7

Solving
-2 + 1x = 7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + 2 + 1x = 7 + 2

Combine like terms: -2 + 2 = 0
0 + 1x = 7 + 2
1x = 7 + 2

Combine like terms: 7 + 2 = 9
1x = 9

Divide each side by '1'.
x = 9

Simplifying
x = 9

See similar equations:

| 2x+x^2=0.051216343 | | sqrt(60)*sqrt(y/4) | | v/9=3/7 | | (4a+4b+4c)(4a+4b+4c)= | | 86=-5-7(-4n-5) | | 30+50x=65x | | 17.42(p)=8.71 | | 4.13-0.54x=5x-2.795 | | 2w+8x-15y+7w+7x+8y= | | 3(1+-0.5y)+4y=-7 | | 5x+4y+9=0 | | x+16-64= | | x*(3x)^1/2 | | 3C^3-24= | | 2x-7/3=-3 | | 2x-7/7=-3 | | x-4/4=9 | | ((7x-1)^(1/2))^2 | | -3/42-x/53/4 | | 5x-20=-3x+68 | | 3y=(x-20) | | 61000+1.30x=19x | | 0.43=x*0.24 | | 1/5=2/3×w | | 1100+0.06x=0.11x | | 2x+6=3x+31 | | sin(x)=-0.48 | | 3h+10=13 | | 60=5x-100 | | 2x+9=5x-19 | | 4(x-9)-3(2x+5)=4.5(2x-15) | | 4(x-5)-3(2x+9)=1.5(2x-9) |

Equations solver categories